Evaluasi Dan Mentoring Dalam Kepemimpinan Sekolah Untuk Meningkatkan Mutu Pendidikan - Agus Sriyani; Raudatur Ridha (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
School leadership plays a crucial role in improving the quality of education. In efforts to strengthen the capacity of school principals as agents of change, a strategic, structured, and sustainable approach is required. This article aims to examine the role of evaluation and mentoring in school leadership as mechanisms for enhancing the quality of educational management. Through a literature review and conceptual analysis, this article concludes that the synergy between evaluation and mentoring significantly contributes to the professional development of school principals and has a positive impact on the overall performance of educational institutions.